Physical mesomechanics of heterogeneous media and computer-aided design of materials (Cambridge International Science, 1998)
The fundamentals of a new science - physical mesomechanics of heterogeneous media - are explained in the book. Mesomechanics is developed at the boundary between the mechanics of continuum and the physics of plasticity and strength of solids and examines the stressed material as a multilevel system in which micro-, meso- and macro levels are organically linked. Mesomechanics is the basis of the computer-aided design of materials with required properties. Examples of application of the new approach to developing constructional and other types of materials are described. The book will be of considerable interest to experts in the area of mechanics and physics of plasticity and strength of materials and physical and applied materials science. -- Provided by publisher.